Improving Health Promotion Using Quality Improvement Techniques in Australian Indigenous Primary Health Care - Percival, Nikki; O’Donoghue, Lynette; Lin, Vivian; Tsey, Komla; Bailie, Ross Stewart (Frontiers in Public Health, 2016)
While some areas of clinical health care are becoming adept at implementing continuous quality improvement (CQI) projects, there has been limited experimentation of CQI in health promotion. In this study, we examined the impact of a CQI intervention on health promotion in four Australian Indigenous primary health care centres. Our study objectives were to: (a) describe the scope and quality of health promotion activities; (b) describe the status of health centre system support for health promotion activities; and (c) introduce a CQI intervention and examine the impact on health promotion activities and health centres systems over two years. Baseline assessments showed sub-optimal health centre systems support for health promotion and significant evidence-practice gaps. After two annual CQI cycles, there were improvements in staff understanding of health promotion and systems for planning and documenting health promotion activities had been introduced. Actions to improve best practice health promotion, such as community engagement and intersectoral partnerships, were inhibited by the way health centre systems were organized, predominately to support clinical and curative services. These findings suggest that CQI can improve the delivery of evidence based health promotion by engaging front line health practitioners in decision making processes about the design/redesign of health centre systems to support the delivery of best practice health promotion. However, further and sustained improvements in health promotion will require broader engagement of management, senior staff and members of the local community to address organisational and policy level barriers.